Implementation of the Read, Answer, Discuss, Explain, and Create (RADEC) Learning Model in Mathematics in Grade IV Elementary School - Nur Aida; Kasman Kasman; Marwah Marwah (Lembaga Yasin AlSys, 2025)
This study investigates the implementation of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model in Grade IV Mathematics instruction and identifies the supporting and inhibiting factors influencing its application. The research is motivated by the low levels of student participation and critical thinking in Mathematics learning, which remains heavily reliant on lecture-based methods. The RADEC model was selected for its emphasis on active, collaborative learning and its alignment with 21st-century skill development. Employing a descriptive qualitative approach, data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities. The implementation process follows five core stages: reading, answering, group discussion, explanation, and creative tasks. Key supporting factors include well-prepared teaching materials, teacher competence, student readiness, increased student engagement, and enhanced self-confidence. In contrast, inhibiting factors comprise limited instructional time, student difficulties during discussions, and challenges in understanding mathematical symbols. Additionally, some students perceived the model as overly serious and time-consuming. The study concludes that while the RADEC model positively influences student engagement and learning outcomes, its success depends on effective time management and adaptive teaching strategies that address students’ cognitive and emotional needs.